Frequency of depression and urinary incontinence in patients of a highly complex institution in Callao, Peru - Paz-Caldas, María Alejandra (2020)
Introduction: The objective of this research was to explore the association between the presence of depressive symptoms and the existence of symptoms suggestive of urinary incontinence in a group of women treated in a public hospital in Peru. Material and Methods: Cross-sectional study was conducted in women with “Seguro Integral de Salud” who attended the gynecology consultation room of Hospital Nacional Daniel Alcides Carrión during November and December of 2018. A sample was calculated with Epidat version 3.1 and the participants were selected by convenience. The main variables of interest were urinary incontinence and depression, both measured by validated measurement instruments: ICIQ-SF and self-assessment scale for Zung depression, respectively. Fisher's exact and Kruskall-Wallis were used to explore the association. Results: A total of 186 women aged between 40 and 60 years were studied. A total of 176 women (94,6%) defined themselves as incontinent and 183 as depression (98,4%). No association was found between the symptoms suggestive of depression with symptoms suggestive of urinary incontinence (p>0,05), but there was an association between the degree of depressive symptoms and the incontinence score (p = 0,0001). Conclusions: A considerable proportion of women suffer from depressive symptoms and urinary incontinence. On the other hand, there seems to be a possible association between urinary incontinence score and the severity of depressive symptoms. More studies are needed to explore this possible association to elucidate the impact that urinary incontinence has on the mood of women in Peru.